Mutations in HID1 Cause Syndromic Infantile Encephalopathy and Hypopituitarism. Issue 1 (5th June 2021) - Schänzer, Anne; Achleitner, Melanie T.; Trümbach, Dietrich; Hubert, Laurence; Munnich, Arnold; Ahlemeyer, Barbara; AlAbdulrahim, Maha M.; Greif, Philipp A.; Vosberg, Sebastian; Hummer, Blake; Feichtinger, René G.; Mayr, Johannes A.; et al.
Abstract : Objective: Precursors of peptide hormones undergo posttranslational modifications within the trans‐Golgi network (TGN). Dysfunction of proteins involved at different steps of this process cause several complex syndromes affecting the central nervous system (CNS). We aimed to clarify the genetic cause in a group of patients characterized by hypopituitarism in combination with brain atrophy, thin corpus callosum, severe developmental delay, visual impairment, and epilepsy. Methods: Whole exome sequencing was performed in seven individuals of six unrelated families with these features. Postmortem histopathological and HID1 expression analysis of brain tissue and pituitary gland were conducted in one patient. Functional consequences of the homozygous HID1 variant p.R433W were investigated by Seahorse XF Assay in fibroblasts of two patients. Results: Bi‐allelic variants in the gene HID1 domain‐containing protein 1 ( HID1 ) were identified in all patients. Postmortem examination confirmed cerebral atrophy with enlarged lateral ventricles. Markedly reduced expression of pituitary hormones was found in pituitary gland tissue. Colocalization of HID1 protein with the TGN was not altered in fibroblasts of patients compared to controls, while the extracellular acidification rate upon stimulation with potassium chloride was significantly reduced in patient fibroblasts compared to controls. Interpretation: Our findings indicate that mutations in HID1 cause an early infantile encephalopathy with hypopituitarism as the leading presentation, and expand the list of syndromic CNS diseases caused by interference of TGN function. ANN NEUROL 2021;90:149–164